2022
DOI: 10.1097/meg.0000000000002475
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predisposing factors for de novo post-COVID-19 irritable bowel syndrome

Abstract: Objective Postinfectious irritable bowel syndrome (IBS) is a known entity. We evaluated the incidence of post-COVID-19 IBS in patients discharged from the hospital and analyzed its correlation with the clinical and laboratory parameters, and treatment during the hospital stay. Methods Three hundred three COVID-19 hospitalized patients without prior history of IBS were prospectively followed after their discharge and were evaluated as per Rome-IV criteria for IBS. Results One hundred seventy-eight patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Our meta-analysis found that there were some predisposing factors for IBS following SARS-CoV-2 infection including depression or anxiety, PCT. Some studies found that moderate to severe patients with COVID-19 tend to have more GI manifestations and IBS [19,21,22,28]. But our study found that disease activity was not associated with IBS following SARS-CoV-2 infection.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Our meta-analysis found that there were some predisposing factors for IBS following SARS-CoV-2 infection including depression or anxiety, PCT. Some studies found that moderate to severe patients with COVID-19 tend to have more GI manifestations and IBS [19,21,22,28]. But our study found that disease activity was not associated with IBS following SARS-CoV-2 infection.…”
Section: Discussioncontrasting
confidence: 86%
“…Patients with IBS have a three-fold increased odd of either anxiety or depression, compared to healthy subjects. Some studies found that oxygen therapy during hospital stay was found to be positively correlated with the development of IBS following SARS-CoV-2 infection [3,28]. Oxygen therapy in SARS-CoV-2 infection depicts significant inflammation and keeping in mind the fact that ACE2 receptors are also present on GI epithelial cells, such intestinal inflammation can lead to long-term GI manifestations [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to noninfectious IBS, the risk is higher in female patients. The presence of severe disease markers, such as an oxygen requirement and high procalcitonin levels, increases the risk of post-COVID-19 IBS[ 49 ]. Another similar study reported that patients with dyspnea at time of admission and a history of allergies and chronic treatment with proton pump inhibitors had an increased risk of developing post-COVID-19 IBS[ 50 ].…”
Section: Pi-ibs General Datamentioning
confidence: 99%
“…The long-term gastrointestinal (GI) consequences are less common chronic morbidities following COVID-19. However, the development of disorders of gut–brain interaction (DGBI), formerly called functional GI disorders (FGID), has been hypothesized and reported following COVID-19 (Table 1) [2 ▪▪ ,3 ▪▪ ,4,5,6,7 ▪▪ ,8–14]. In this paper, we will review the literature on post-COVID-19 DGBI…”
Section: Introductionmentioning
confidence: 99%